The design, development and evaluation of a virtual reality (VR)-based learning environment: Its efficacy in novice car driver instruction. - Chen, Chwen Jen; Toh, S.C.; Wan, M.F. (2005)
The potential of VR technology for instructional use is gaining recognition from both researchers and practitioners of this field. This paper looks into the design, development and evaluation issues of a VR-based learning environment. It suggests a feasible instructional design theoretical framework to guide the instructional design of a VR-based learning environment, a constructivist instructional development model to guide the design and development process of such learning environment, and provides another evidence of the positive instructional effect of this technology for instructional use.